2018
DOI: 10.1176/appi.ajp.2018.17080858
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Proteome Compensation and Resilience to Psychosis in Alzheimer’s Disease

Abstract: Accumulation of synaptic proteins, particularly those that are enriched in the postsynaptic density, is associated with resilience to psychosis in Alzheimer's disease. One candidate mechanism for this synaptic proteome compensation is alteration in levels of proteins that facilitate the transport of synaptic proteins to and from the postsynaptic density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 42 publications
4
56
0
Order By: Relevance
“…Recent studies have shown that reductions in kalirin are associated with improvements in psychosis-associated behaviours in AD mouse models, supporting earlier findings in postmortem tissue [63, 64•]. Notwithstanding the challenges and complexities of assessing the AD psychosis phenotype in animal models, these findings indicate novel pathways, such as synaptic resilience, which warrant further investigation [65]. They also highlight the value of preclinical testing in identifying such mechanisms.…”
Section: Kalirinsupporting
confidence: 78%
“…Recent studies have shown that reductions in kalirin are associated with improvements in psychosis-associated behaviours in AD mouse models, supporting earlier findings in postmortem tissue [63, 64•]. Notwithstanding the challenges and complexities of assessing the AD psychosis phenotype in animal models, these findings indicate novel pathways, such as synaptic resilience, which warrant further investigation [65]. They also highlight the value of preclinical testing in identifying such mechanisms.…”
Section: Kalirinsupporting
confidence: 78%
“…99 We have previously reported that the presence of comorbid TDP43 pathology in AD is independently associated with psychosis risk. 100 We previously identified, and independently replicated, an inverse association between polygenic risk for schizophrenia, defined by a limited set of schizophrenia risk SNPs 69 , and risk for psychosis in AD. 28 It was thus somewhat surprising that we saw a non-significant genetic correlation between these two disorders when considering both a larger set of SNPs and a substantially enlarged cohort of AD subjects with and without psychosis.…”
Section: Discussionmentioning
confidence: 88%
“…Elevated total CSF tau levels have been reported in AD patients with psychosis versus AD patients without psychosis, although there were no differences in amyloid beta protein levels or phosphorylated tau levels [92]. Neuropathological studies additionally seem to support a role for phosphorylated tau in AD patients with psychosis, thus suggesting it may serve as a useful biomarker in future studies [93]. CSF biomarkers of amyloid and tau may also be useful in differentiating psychosis related to AD versus psychosis related to a psychiatric condition in older adults [94].…”
Section: Biomarker Studiesmentioning
confidence: 89%
“…CSF biomarkers of amyloid and tau may also be useful in differentiating psychosis related to AD versus psychosis related to a psychiatric condition in older adults [94]. No prior studies have used amyloid or tau PET tracers to investigate regionally specific neuropathological markers of psychosis in dementia, though evidence linking psychosis in AD to phosphorylated tau suggests this may be a useful approach [61,92,93]. There is a suggested link of psychosis with vascular and Lewy body pathology based on postmortem data though replication with in vivo samples is required [95].…”
Section: Biomarker Studiesmentioning
confidence: 99%